SOCIAL SUPPORT AND PSYCHOLOGICAL ADAPTATION FOR NEW CHINESE FEMALE STREAMERS: THE MEDIATING EFFECTS OF PROFESSIONAL IDENTITY AND MODERATING EFFECT OF PSYCHOLOGICAL CAPITAL - ZHENG, ZHEYUN; A. JOHNSON, DONALD (Scholar: Human Sciences, 2022)
In China, internet streaming has become an entertainment medium for everyone, and as an emerging profession, streamers are experiencing varying degrees of psychological distress. This research focused on four dimensions: social support, psychological capital, professional identity, and psychological adaptation. Factor analysis and reliability analysis were used to evaluate the psychometric properties of the revised scale; ANOVA and t-tests were also used to evaluate the effects of age, region, education, and full-time vs. part-time employment. Regression analysis was used to evaluate the relationship between the four latent variables. The results showed significant differences in Chinese new female streamers’ age, region, education level, and job type (full-time or part-time streaming). Results showed that social support had positive predictive effects on psychological adaptation, professional identity was a significant mediator of social support with psychological adaptation, and psychological capital played a significant moderating role between dimensions. The media industry involved in the work of Chinese streamers should pay more attention to the psychological health of the streamers, track the psychological adaptability of the streamers to help prevent their psychological problems, and provide them with counseling promptly. Work standardization of the entire streaming industry should be improved so that streamers and the entire industry can continue to develop healthily.